Improving Self-Care and Self-Efficacy in Type 2 Diabetes Mellitus Patients by Online DSME Educational Videos - Virman Kurnia Tisna; Emma Kamelia; Dewi Aryanti (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2025)
Approximately 39.2% of individuals diagnosed with diabetes experience complications. The most common complication reported is diabetic foot, affecting 43.4% of those with complications, followed by nephropathy at 29.5%. Diabetes Self-Management Education (DSME) is essential in type 2 diabetes care, as it equips patients with the skills and confidence needed to manage their condition effectively, thereby reducing complications, enhancing quality of life, and minimising healthcare costs. This study aimed to determine the effect of DSME online educational videos on self-care and self-efficacy of type 2 DM patients. A quasi-experimental study was conducted among 696 diabetic type 2 outpatients from February to March 2023. The patient was selected for purposive sampling from Tamansari Health Center Tasikmalaya Regency. The intervention group (n = 21) received 1 week of online videos about DSME health education in every day. The control group (n = 21) received regular health education in Tamansari Health Centre as care services. Data were collected using The Summary of Diabetes Self-Care Activities (SDSCA) and Diabetes Management Self-Efficacy Scale (DMSES) questionnaires. Data were analysed using paired t-test and independent t-test analysis. There is an effect after being given online DSME educational videos on self-care and self-efficacy of type 2 DM patients with a significance value of self-care and self-efficacy p = 0.000 (p <0.05), it can be concluded that the use of online DSME educational videos affects increasing self-care and self-efficacy of type 2 DM patients.